Using Joomla efficiently build and manage custom websites - Severdia, Ron; Gress, Jennifer (O'Reilly Media, 2014)
If you're new to content management systems - or even new to building websites - this practical guide will get you up and running in no time. You don't have to know much code, if any, to get started.